A New Website for Cartographic Resources — CartoMundi - Arnaud, Jean-Luc (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
For about two years, the Maison Méditerranéenne des Sciences de l'Homme — MMSH — in Aix-en-Provence has been developing a new website — CartoMundi — dedicated to cartographic documents. This site is organised around a tool able to identify and select documents according to the geographical zone they really represent. Each series is described by a unique notice and a key map. CartoMundi is a collective project; it consists of an open network of members. It will offer easy access to largely unknown documents and should encourage the use of cartography, both as a resource and as a research subject.